Sidon to Tyre: the Macedonian administration and relative chronology - Taylor, Lloyd W. H. (KOINON: The International Journal of Classical Numismatic Studies, 2020)
This essay summarizes the chronology of the dated Alexander tetradrachms of Sidon and Tyre (Ake of Newell and Price), including the implications of recent analysis of the Achaemenid dating era applicable to Tyre. It details a newly identified die link between the first issue of each mint, one that sheds light on the approach of the Macedonians to the establishment of a mint at Tyre following the successful siege of the city.